OverProt: secondary structure consensus for protein families - Midlik, Adam; Hutařová Vařeková, Ivana; Hutař, Jan; Chareshneu, Aliaksei; Berka, Karel; Svobodová, Radka (Bioinformatics (Oxford, England), 2022)
SUMMARY: Every protein family has a set of characteristic secondary structures. However, due to individual variations, a single structure is not enough to represent the whole family. OverProt can create a secondary structure consensus, showing the general fold of the family as well as its variation. Our server provides precomputed results for all CATH superfamilies and user-defined computations, visualized by an interactive viewer, which shows the secondary structure element type, length, frequency of occurrence, spatial variability and β-connectivity. AVAILABILITY AND IMPLEMENTATION: OverProt Server is freely available at https://overprot.ncbr.muni.cz. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Computers; Software; software; Consensus; počítače; proteiny; Protein Structure, Secondary; konsensus; Proteins; sekundární struktura proteinů